Social Ethics In The Story Of Prophet Yusuf And Its Relevance To Millennial Youth Semiotic Analysis Of Umberto Eco's Communication - Susilo Sudarman (Universitas Islam Negeri (UIN) Mataram, 2023)
Millennial youth are faced with the trend of technological development, one side of technology has a significant impact on the lives of modern society. On the other hand, technological developments have a negative impact on society, at all social levels, both adults, adolescents and children. Developments that occur in all aspects of human life form the character of social communication which tends to be limited to electronic media rather than direct communication. This is a problem in itself for the formation of people's character in communicating with one another. Changes in the way of communication then have an impact on the character and activities of modern society, which then affects the millennial young generation. The loss of respect, mutual respect, mutual protection, mutual cooperation, is a very thick thing with the millennial young generation. In this study, the author uses the semiotic pattern of Umberto Eco communication contained in QS. Joseph. This paper sees that the content contained in Q.S Yusuf teaches that today's young people known as millennials must keep their eyes, close their eyes, be patient and others.